EVALUATION ON EFFECTIVENESS OF ALLOCATING ESTIMATIONS OF FORESTRY REVENUE SHARING (A Case Study on Intergovernmental Fiscal Transfers in Directorate General of Fiscal Balance, Ministry of Finance) - Kusuma Dewi, Triana (FIA UB, 2015)
Evaluation On Effectiveness Of Allocating Estimations Of Forestry Revenue Sharing(A Case Study on Intergovernmental Fiscal Transfers in Directorate General of Fiscal Balance, Ministry of Finance). Ineffective estimated allocation of forestry revenue sharing is accused of leading the presence of local governmentâs debt. The difficulty in creating a fair share of revenue sharing and poor procedure for the estimations also are criticized by some literature reviews. Objective of this study is to identifying the effectiveness of allocating estimation of forestry revenue sharing in Indonesia by using a qualitative description analysis method by examines data from 2010 to 2012. This study was done by case study on Intergovernmental fiscal transfers in Directorate General Fiscal Balance Ministry of Finance, Jakarta. It discovered coordination, partnerships, hierarchical systems, and job descriptions are influencing in the estimation making progress.This study insists on the necessity of coordination within central government and between central and local governments, a framework schedule and the validity of data sources. Finally, an e-governmental tools and an econometric formula should be included in the estimation process.